STUDI KONTRIBUSI DAN EFEKTIVITAS PENERIMAAN BUMD DALAM UPAYA PENINGKATAN PAD DI PROVINSI SULAWESI TENGGARA - Shely Puspita Sari; Muh. Yani Balaka; Syamsir Nur (Universitas Halu Oleo, 2021)
This study aims to determine the contribution and effectiveness of Regional Owned Enterprises in Southeast Sulawesi and the factors that influence it. Data analysis methods used are contribution analysis, effectiveness analysis and descriptive analysis. BFor the average revenue per BUMD at PT. BPD Sultra by 96.79 percent is in the very good category, PERUMDA Utama Sultra by 1.59 percent is in the very poor category, BPR Bahteramas by 1.50 percent is in the very poor category, and PT. Askrida Insurance is 0.10 in the very poor category. For the effectiveness produced by BUMD on the results of separated regional wealth management in Southeast Sulawesi during 2014- 2019, an average of 101.21 percent was in the very effective category. For the factors that influence the contribution, namely the realization generated by each BUMD in Southeast Sulawesi Province. And for the level of effectiveness, namely the difference in targets and realization, the difference in capital participation by the government or third parties, the type of business characteristics of the BUMD concerned.